'If nurses were in our shoes would they breastfeed their own babies?' A qualitative inquiry on challenges faced by breastfeeding mothers on the PMTCT programme in a rural community in Zimbabwe - Zibusiso Nyati-Jokomo; Inam Chitsike; Elizabeth Mbizvo; James January (BMC, 2019)
Abstract Background The Prevention of Mother to Child Transmission (PMTCT) of HIV programme in Zimbabwe has had remarkable success despite the country's economic challenges. The aim of this study was to explore the challenges faced by breastfeeding mothers on the PMTCT programme. Method Narratives from 15 women (age range 19-35 years) were collected at two rural health facilities in Zimbabwe through in-depth interviews over a period of 6 months. Thematic analysis was used to describe breastfeeding mothers' experiences and challenges of being on the PMTCT programme. Results The findings suggest that breastfeeding women on the PMTCT programme face challenges that include internal, external and institutional stigma and discrimination. Women reported a sense of powerlessness in decision making on following through with the PMTCT programme and were ambivalent regarding disclosure of their HIV status to their partners and significant others. Conclusion HIV and AIDS programmes should pay attention to women's readiness for interventions. There is need to understand women's life experiences to ensure informed and targeted programming for PMTCT.